PCR-Based Legionella Risk Evaluation of Drinking Water Systems—An Empirical Field Evaluation - Markus Petzold; Nicole Zacharias; Sarah Uhle; Laurine Kieper; Nico Tom Mutters; Thomas Kistemann; Christiane Schreiber (Microorganisms)
Pathogens in water systems pose potential health risks. Several countries provide guidelines and risk management strategies for clean water systems. Regarding legionellae, culture-based methods are still the gold standard, whereas molecular methods such as quantitative real-time PCR (qPCR) are controversially discussed among experts as an alternative. It remains questionable as to whether monitoring by qPCR contributes to sustainable water hygiene and effective health prevention. Drinking water samples from 101 buildings were culture-based analyzed to determine the legionellae concentration, along with qPCR tests. The negative predictive values for Legionella spp. and L. pneumophila qPCR regarding the cultivation method were 100% and 98%, respectively. As Legionella spp. DNA is ubiquitously detected, the positive predictive value was low. L. pneumophila DNA was in 18% of the drinking water samples detected by qPCR, among which only 7% was quantifiable. Neither gold-standard methods of cultivation nor qPCR methods alone are suitable to monitor the risk to health by legionellae in water environments adequately. To overcome methodical difficulties, the benefits of a strategic integration of qPCR alongside cultivation methods should be applied to develop a comprehensive protocol for the stepwise analysis of water samples, which can be implemented in international regulatory frameworks in the future.